LOWER LIP CANCER - A CASE REPORT - Rosen Tsolov; Georgi Yordanov; Silvia Tsvetkova-Trichkova; Iliya Peev (Peytchinski Publishing, 2020)
A case report of a patient with cancer of the lower lip is presented. The reason for the treatment is an entity in the lower lip. It has been dating for several months and has grown significantly lately. Due to the complicated, inflammatory process, he was treated in the clinic, and after the same subsidence, he was admitted for surgical treatment. Surgery performed Resectio Partialis Labii Inferioris and plastics "a modo Bernard". The case was presented to an oncology council, establishing that the patient was being monitored and he was given recommendations for a hygienic diet. The patient was discharged with improvement.